The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ardp.201300183
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antibacterial, and Antiviral Evaluation of New Heterocycles Containing the Pyridine Moiety

Abstract: A facile one-pot four-component reaction was utilized to construct 2-oxo-1,2-dihydropyridine-3-carbonitrile as a scaffold for the synthesis of many fused heterocyclic systems, namely, furopyridine, pyridothiadiazepinthione, and pyridotriazine, as well as non-fused heterocyclic systems such as phthalazin-2(1H)-ylnicotinonitrile, pyridin-2-yl-1H-pyrazole, and pyrazol-1-ylnicotino-nitrile,1-(3-cyanopyridin-2-yl)-1H-pyrazole. The new compounds were evaluated as antimicrobial and antiviral agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 26 publications
(26 reference statements)
0
28
0
Order By: Relevance
“…Nitrogen‐containing heterocyclic compounds, which are involved in an extraordinarily wide range of reaction types in vitro and in vivo, constitute many important structural units of marketed drugs. The clinical applications of these compounds include anti‐bacterial, anti‐viral, anti‐fungal, anti‐inflammatory, and anti‐tumour drugs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen‐containing heterocyclic compounds, which are involved in an extraordinarily wide range of reaction types in vitro and in vivo, constitute many important structural units of marketed drugs. The clinical applications of these compounds include anti‐bacterial, anti‐viral, anti‐fungal, anti‐inflammatory, and anti‐tumour drugs …”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Nitrogen-containing heterocyclic compounds, which are involved in an extraordinarily wide range of reaction types in vitro and in vivo, constitute many important structural units of marketed drugs. The clinical applications of these compounds include anti-bacterial, 16 anti-viral, 17 anti-fungal, 18 anti-inflammatory, 19 and anti-tumour drugs. 20,21 In our current research, we screened a pool of nitrogencontaining heterocyclic compounds [22][23][24][25] (Table S1) and found that 4-(4-fluorophenyl)-2-phenyl-5, 6, 7, 8-tetrahydroquinoline (FPTHQ), 23 can specifically induce senescence in ovarian cancer cells in a dosedependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Thiadiazole is a well-known pharmacophore endowed with diverse pharmacological activities such as antibacterial [13,14], antifungal [15], anticancer [16], antimalarial [17], and anti antidiabetic [18]. On the contrary, pyrazole is also reported to be present in many active pharmaceutical agents displaying myriad activities such as antioxidant [19,20], antimycobacterial [21], antiviral [22,23], anticonvulsant [24], and antibacterial [25]. These 2 pharmacophores, that is, thiadiazole and pyrazole, also showed potent inhibition of NF-κB [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Many of heterocyclic compounds are known as anticancer drugs such as alkylating agents which have targeted cell DNA causing cell death. Heterocycles 1 structures are composed by atoms other than carbon, where the most times substituents are sulfur, oxygen 1 and nitrogen 1,2 .The model size of heterocycles ring, together with the substituent group of the core scaffold 2 , impact tightly on the chemical and physical properties 3 while among the clinical applications, heterocyclic compound has an active role as anti-bacterial 4,5 , anti-viral 6 , anti-fungal 7 , antiinflammatory 8 and anti-tumor drugs [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%